2021
DOI: 10.1017/s0950268821000066
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of case-fatality rate in COVID-19 patients with hypertension and diabetes mellitus in the New York state: a preliminary report

Abstract: Pre-existing health conditions may exacerbate the severity of coronavirus disease 2019 (COVID-19). We aimed to estimate the case-fatality rate (CFR) and rate ratios (RR) for patients with hypertension (HBP) and diabetes mellitus (DM) in the New York state. We obtained the age-specific number of COVID-19 confirmed cases and deaths from public reports provided by the New York State Department of Health, and age-specific prevalence of HBP and DM from the Behavioral Risk Factor Surveillance System 2017. We calcula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…Our results suggest that elevated HRs associated with comorbidities are more marked in the younger age groups and, as reported by Ge et al 14 , the young population with comorbidities should also be considered as a vulnerable group. In addition, our results suggest a strong association between the level of education and fatality risk due to COVID-19, showing that strategies for the prevention and management of the disease also need to consider the social aspects of the population.…”
supporting
confidence: 86%
“…Our results suggest that elevated HRs associated with comorbidities are more marked in the younger age groups and, as reported by Ge et al 14 , the young population with comorbidities should also be considered as a vulnerable group. In addition, our results suggest a strong association between the level of education and fatality risk due to COVID-19, showing that strategies for the prevention and management of the disease also need to consider the social aspects of the population.…”
supporting
confidence: 86%
“…In contrast, a whole-population study from England found only 5.2% DM between COVID-19 patients [36] . In American countries, the US presented the highest prevalence rates, approximately 12% to 30% [37] , [38] , while in Latin America, DM has been reported in 8.3% of COVID-19 cases [39] . Additionally, studies from London and the US said that nonwhite patients with DM were the majority among COVID-19 cohorts, with 72% and 56%, respectively [40] , [41] .…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, studies from London and the US said that nonwhite patients with DM were the majority among COVID-19 cohorts, with 72% and 56%, respectively [40] , [41] . Furthermore, the prevalence of DM in COVID-19 patients has been higher in adults over 50 years of age, especially in those aged 65-70 years [29] , [30] , [33] , [37] , [42] . Other studies indicate that male patients with DM had a significant prevalence (50–60%) among COVID-19 patients [31] , [42] , [43] .…”
Section: Introductionmentioning
confidence: 99%
“…Pre-existing health conditions may exacerbate the severity of SARS-CoV-2 disease. These conditions include old age [ 4 ], hypertension, coronary artery disease, and diabetes mellitus [ 5 , 6 , 7 ]. Moreover, weather conditions, such as a cold climate, humidity [ 8 , 9 ], and environmental pollution are leading causative factors in increasing SARS-CoV-2 cases and deaths [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%